Impact of Psychological Factors on the Performance of Athletes with Amblyopia: Mediation of Athletes’ Satisfaction - Ayhan ÖNAL (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Amblyopia is a disorder of the eye that may affect a person's vision. It has been noticed that athletes with amblyopia are frequently denied access to higher chances. Hence, individuals experience psychological anguish, which negatively affects their overall performance. Many psychological elements have a significant effect on the performance of athletes. This prompted the current study to examine the link between several psychological aspects (competition and commitment) and athletes' performance, emphasizing the function of players' pleasure as a mediator. 560 Iraqi athletes with amblyopia from various locations were surveyed to acquire data for the present study, which employed a quantitative approach and a survey methodology. The email was used to disseminate the surveys, and data was collected. After data collection, several statistical tools and methods were utilized to conduct statistical analysis. The "Partial Least Square" (PLS) approach was used to evaluate the proposed hypotheses. Several psychological aspects (such as dedication and competitiveness) have a major effect on the performance of athletes, as demonstrated by the current study's findings. Athletes' pleasure strongly moderated the association between psychological characteristics (such as commitment and competitiveness) and athletes' performance.